Intraocular pressure and central corneal thickness in full-term newborns - Ferreira,Claudia Cardoso Maestri (2017)
ABSTRACT Objective: The aim of this study was to determine the central corneal thickness (CCT) and intraocular pressure (IOP) in full-term newborns and to correlate these values with the following variables: weight, sex, and post-conception age (PCA). Methods: IOP and CCT were determined in 52 full-term newborns with a mean gestational age of 39.43 ± 1.03 weeks and a mean birth weight of 3,273 ± 558 g. The mean age of the neonates at the time of taking the measurements was 1.15 ± 1.38 days after birth. IOP was determined with a Tono-Pen, and CCT was determined using a handheld ultrasound pachymeter. Results: The mean overall IOP was 14.0 ± 2.91 mmHg, and the mean IOP in male and female newborns was 13.77 ± 2.88 mmHg and 14.32 ± 3.05 mmHg, respectively. The mean overall CCT was 605.87 ± 62.98 µm, and the mean CCT in male and female newborns was 626.70 ± 67.46 µm and 577.45 ± 45.50 µm, respectively; the mean CCT was higher in male newborns than in female newborns. PCA was negatively associated with CCT, IOP, and weight; however, only the correlation with CCT was statistically significant. Comparisons between the sexes showed significant differences for two variables: weight and CCT. Conclusions: No relationship was found between CCT and IOP; however, we found a positive association between weight and CCT.